Chemical composition, antioxidant and biological activity of Ocotea bicolor Vattimo-Gil (LAURACEAE) essential oil - Carolina Sette Barbosa Damasceno; Letícia Freire de Oliveira; Ellis Marina Szabo; Ângela Maria Souza; Josiane Fatima Gaspari Dias; Marilis Dalarmi Miguel; Obdúlio Gomes Miguel (Universidade de São Paulo, 2018)
ABSTRACT The essential oil composition of the Ocotea bicolor, native plant of Brazil, was studied for the first time. The essential oil of the leaf was obtained by hydrodistillation and analyzed by GC/MS. The analytical procedure revealed a predominance of sesquiterpenes, δ-cadinene (7.39%), β-sesquiphellandrene (6.67%), β-elemene (5.41%) and α-cadinol (5,23%). The essential oil was submitted to brine shrimp toxicity evaluation, antioxidant and antibacterial tests. The antioxidant activity by the formation of phosphomolybdenum complex method presented positive results. The minimum inhibitory concentration (MIC) values were higher than 1000 μg/mL for the microorganisms tested. Toxicity activity revealed LC50 results of 40.10 (μg/mL), being toxic to the organisms in this study.